Intelligent transport system in smart cities : aspects and challenges of vehicular networks and cloud /: aspects and challenges of vehicular networks and cloud. ([2018]) - Meneguette, Rodolfo I; De Grande, Robson E; Loureiro, Antonio Alfredo Ferreira, 1961-
No abstract available